2017
DOI: 10.1021/acs.analchem.7b00599
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Driven Control of Metabolite Selectivity Using Nanostructure-Initiator Mass Spectrometry

Abstract: Nanostructure-initiator mass spectrometry (NIMS) is a laser desorption/ionization analysis technique based on the vaporization of a nanostructure-trapped liquid "initiator" phase. Here we report an intriguing relationship between NIMS surface morphology and analyte selectivity. Scanning electron microscopy and spectroscopic ellipsometry were used to characterize the surface morphologies of a series of NIMS substrates generated by anodic electrochemical etching. Mass spectrometry imaging was applied to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…On the basis of the optimization process of the WS 2 -assisted LDI-MS platform, it was identified that the sensitivity is greatly influenced by the thickness of the deposited TMD material. Although many studies reported the successful analysis of biomolecules using inorganic nanomaterials as alternative matrixes, however, the analytical sensitivity that the nanomaterials can provide is a key issue for their practical applications. In many cases, it is ambiguous to define the major factor that limits the analytical sensitivity of nanomaterials because the method of deposition is as significant as the physicochemical properties of the material itself. The microliquid dispenser inkjet system adopted in this study is capable of controlling the volume of deposition in picoliter scales with excellent uniformity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the optimization process of the WS 2 -assisted LDI-MS platform, it was identified that the sensitivity is greatly influenced by the thickness of the deposited TMD material. Although many studies reported the successful analysis of biomolecules using inorganic nanomaterials as alternative matrixes, however, the analytical sensitivity that the nanomaterials can provide is a key issue for their practical applications. In many cases, it is ambiguous to define the major factor that limits the analytical sensitivity of nanomaterials because the method of deposition is as significant as the physicochemical properties of the material itself. The microliquid dispenser inkjet system adopted in this study is capable of controlling the volume of deposition in picoliter scales with excellent uniformity.…”
Section: Resultsmentioning
confidence: 99%
“…To deal with these limitations, several types of nanomaterials such as metal nanoparticles, carbon-based nanomaterials, and silicon-based nanostructures have been investigated in LDI-MS and have demonstrated feasibility for the analysis of biomolecules including peptides, fatty acids, and pharmaceutical drugs. However, there are several drawbacks that need to be resolved to ensure the applicability of these alternative LDI materials. For example, metal nanoparticles can be unstable in solid states after being deposited onto the target substrate and often require in situ synthesis prior to the analysis, particularly in the case of gold nanoparticles .…”
mentioning
confidence: 99%
“…Identify metabolites based on m/z values, retention time and compound fragmentation patterns using a library of metabolite standards. NOTE: EcoFAB devices made of a 5:1 elastomer base to curing agent mixture with custom clamps (Figure 7A) are used for root stamping onto nanostructure-initiator mass spectrometry (NIMS) chips, 28,29,30 since PDMS layers can be reversely bonded to the surfaces of NIMS chips.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the targeted sample is treated with a fixed wavelength of the laser beam to accomplish the sample desorption and ionization followed by the measurement of m/z ratio of the conditioned analyte via mass spectrometry (Abdelhamid and Wu 2015;Calavia et al 2012;Cheng et al 2012). Therefore, it is necessary for the sample to absorb the specific wavelength of laser light (Etxebarria et al 2014;Gao et al 2017;Greving et al 2011). The optimized LDI-MS technique has high sensitivity and accuracy and can detect up to femtogram (fg) level.…”
Section: Laser Deposition/ionization Mass Spectrometry (Ldi-ms)mentioning
confidence: 99%